THE STRUCTURAL-SEMANTIC MODELS OF PHRASEOLOGICAL UNITS WITH THE COMPONENT “WATER” IN THE RUSSIAN LANGUAGE - Talantвek kyzy Sezim; Мukambetova А. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
This article is dedicated to the analysis of the structural-semantic models of phraseological units with the component "water" in the Russian language. Various structural categories of phraseological units are considered, including verbal, nominative, and comparative constructions. A wide range of semantic meanings associated with the component "water" are analyzed, such as infinity, purity, elemental force, slowness, and danger. The study demonstrates how water is used in phraseological units to convey complex and multifaceted concepts, reflecting the cultural and linguistic characteristics of the Russian people. The examination of these models contributes to a better understanding of the expressive capabilities of the Russian language and its metaphorical resources. Special attention is paid to how these phraseological units may vary depending on context and usage, as well as how they correlate with similar units in other languages. The article also provides examples of the use of phraseological units with the component "water" in literary texts and everyday speech, which helps illustrate their functional ingenuity and diversity. Analysis of the use of contexts helps to identify changes in the dynamics of the meanings of phraseological units and their adaptation to modern realities. In addition, the study uses a moderate cultural context taking into account the phraseological elements and their metaphorical meaning.